Pengembangan E-LKPD Interaktif Berbasis Games Berbantuan Website Wizer.me pada Materi Sistem Pencernaan Manusia - Trio Ageng Prayitno Trio; Nuril Hidayati; Firda Eka Jauharoh (Universitas Nusantara PGRI Kediri, 2024)
Interactive e-LKPD based on games assisted by the Wizer.me website has never been developed by educators in schools. Interactive e-LKPD based on games assisted by the Wizer.me website is thought to increase students' motivation to learn. The purpose of the study was to produce interactive e-LKPD based on games assisted by the Wizer.me website on the human digestive system material. The type of research is development research with the Thiagarajan development model consisting of define, design, develop, and disseminate. However, this study is limited to the develop stage. The research instruments are a needs analysis questionnaire, an evaluation expert validation questionnaire, and a learning media expert validation questionnaire. Interactive e-LKPD based on games assisted by the Wizer.me website on the human digestive system material is declared very valid and feasible in terms of evaluation questions (98%) and learning media (97%). Interactive e-LKPD based on games assisted by the Wizer.me website can be recommended as one of the tools to develop student skills, especially Generation Z where teachers can create more interesting and dynamic learning experiences through the use of technology and digital tools.